Vagus nerve stimulation as a novel treatment for systemic lupus erythematous: study protocol for a randomised, parallel-group, sham-controlled investigator-initiated clinical trial, the SLE-VNS study. Issue 9 (20th September 2022) - Zinglersen, Amanda Hempel; Drange, Ida Lynghøj; Myhr, Katrine Aagaard; Fuchs, Andreas; Pfeiffer-Jensen, Mogens; Brock, Christina; Jacobsen, Søren
Abstract : Introduction: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease. SLE is treated with immunosuppressants with suboptimal efficacy and high risk of serious side effects. Patients with SLE have increased risk of mortality, organ damage and debilitating treatment-resistant fatigue. Autonomic nervous system dysfunction (AD) is present in approximately half of the patients and may promote autoimmunity by weakening the vagally mediated anti-inflammatory reflex. Recent studies suggest that transcutaneous vagus nerve stimulation (tVNS) has few side effects and beneficial effects on fatigue, pain, disease activity and organ function. This study investigates whether adjuvant tVNS improves measures of fatigue (primary end point), AD, clinical disease activity, inflammation, pain, organ function and quality of life. Hence, this study will contribute to the understanding of AD as a potentially important precursor of fatigue, disease activity, progression and complications in SLE, and how tVNS mechanistically may attenuate this. As adjuvant tVNS use may reduce the need for traditional immunosuppressive therapy, this trial may prompt a shift in the treatment of SLE and potentially other autoimmune disorders. Methods and analysis: Eighty-four patients with SLE with fatigue and AD will be randomised 1:1 to active or sham tVNS in this double-blinded parallel-group study. In period 1 (1 week), participants will receive a 4 min tVNS 4 times daily and report on fatigue daily. After a 2-week pause, period 2 (8 weeks) will entail tVNS twice daily and participants will report on fatigue, pain and disease activity weekly. Secondary end points will be assessed before and after each period and after 1 week in period 2. Ethics and dissemination: The study is approved by the Danish Medical Research Ethical Committees (case no: 2120231) and results will be published in international peer-reviewed journals. Trial registration number: NCT05315739 .